UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN ARBENAN (Duchesnea indica (Jacks.) Focke) DENGAN METODE DPPH - Nuraziza Nuraziza; Seniwati Dali; Risda Waris (As-Syifaa Jurnal Farmasi, 2017)
Arbenan (Duchesnea indica (Jacks.) Focke) is a plant belonging to Rosaceae family which server as an antioxidant, flavonoids. This research aimed to determine the antioxidant activity of ethanol extract of arbenan leaves using DPPH. The leaves were extracted using maceration method with a sample size of 300 gs dissolved using ethanol 70%, then obtained the viscous extract of 32,49 gs. The arrest of free radicals for each tested sample under the inhibition of DPPH. The tests were conducted at the 4 concentration series of 10, 20, 30, and 40 ppm by using methanol p.a by the addition of 0,5 mL with 3,5 mL DPPH of 30 ppm. Antioxidant activity absorbance was measured by a spectrophotometer at the wavelength of   515 nm and IC50 value was calculated based on the absorbance data. The calculations showed that the Arbenan leaves have a very strong antioxidant activity with IC50 value of 30,20 µg/mL.